2008
DOI: 10.1002/hep.22795
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antigen cross-presented by liver sinusoidal endothelial cells induces liver-specific CD8 T-cell retention and tolerization

Abstract: Peripheral CD8 T-cell tolerance can be generated outside lymphatic tissue in the liver, but the course of events leading to tolerogenic interaction of hepatic cell populations with circulating T-cells remain largely undefined. Here we demonstrate that preferential uptake of systemically circulating antigen by murine liver sinusoidal endothelial cells (LSECs), and not by other antigen-presenting cells in the liver or spleen, leads to cross-presentation on major histocompatibility complex (MHC) I molecules, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 34 publications
2
64
1
1
Order By: Relevance
“…So far, crosspresentation capacity has been shown for macrophages and DCs and only a few other hematopoietic (e.g., B cells 25 and neutrophils 26 ) and nonhematopoietic (liver sinusoidal endothelial cells 27 ) cell types. In contrast to liver sinusoidal endothelial cells, which induce a liver-specific T cell tolerization, 28 we found that activated podocytes are potent activators of CD8+ T cells. Next, we showed that this finding could also happen in vivo.…”
Section: Discussioncontrasting
confidence: 78%
“…So far, crosspresentation capacity has been shown for macrophages and DCs and only a few other hematopoietic (e.g., B cells 25 and neutrophils 26 ) and nonhematopoietic (liver sinusoidal endothelial cells 27 ) cell types. In contrast to liver sinusoidal endothelial cells, which induce a liver-specific T cell tolerization, 28 we found that activated podocytes are potent activators of CD8+ T cells. Next, we showed that this finding could also happen in vivo.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the ability of non-hematopoietic cells to induce peripheral CD8 + T cell tolerance is not unique to LECs and FRCs. Liver sinusoidal endothelial cells (LSECs) are considered critical for tolerance to food antigens, as they mount CD8 + deletional tolerance against exogenous antigens coming directly from the gut (68,69). Tolerance induction by stromal cells is reminiscent of central tolerance induced in the thymus by stromal medullary thymic epithelial cells (mTECs), a process that is dependent on PTA expression driven by the autoimmune regulator Aire (70).…”
Section: Modulation Of T Cell Activation By Lymphatics Lecs Present Amentioning
confidence: 99%
“…For example, liver sinusoidal endothelial cells (LSECs) are thought to capture and cross-present circulating Ag to CD8 + T cells, leading to CD8 + T cell deletion and the establishment of a tolerogenic environment (14). This is especially important in the liver, where LSECs are among the first cells to encounter the large diversity of foreign Ags from food, as well as TLR agonists from commensal sources (15).…”
mentioning
confidence: 99%